2020
DOI: 10.1245/s10434-020-08659-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI and Whole Slide Image-Based Pretreatment Prediction of Pathological Response to Neoadjuvant Chemoradiotherapy in Rectal Cancer: A Multicenter Radiopathomic Study

Abstract: Background The aim of this work is to combine radiological and pathological information of tumor to develop a signature for pretreatment prediction of discrepancies of pathological response at several centers and restage patients with locally advanced rectal cancer (LARC) for individualized treatment planning. Patients and Methods A total of 981 consecutive patients with evaluation of response according to tumor regression grade (TRG) who received nCRT were retrospectively recruited from four hospitals (prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 36 publications
(46 reference statements)
1
40
0
Order By: Relevance
“…In a preliminary study, we confirmed that integration of radiomics MRI and biopsy slides enhanced the prediction of tumour regression grade to neoadjuvant chemoradiotherapy in patients with locally advanced rectal cancer. 14 However, these results…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In a preliminary study, we confirmed that integration of radiomics MRI and biopsy slides enhanced the prediction of tumour regression grade to neoadjuvant chemoradiotherapy in patients with locally advanced rectal cancer. 14 However, these results…”
Section: Introductionmentioning
confidence: 76%
“…These findings are consistent with those of our previous study, in which we developed a radiopathomics model to predict tumour regression grade for locally advanced rectal cancer. 14 In the present study, RAPIDS was constructed using a modified modelling method with nine rMRI features, 12 pathomics nucleus features, and 18 pathomics microenvironment features. These selected features were not redundant but complementary, as shown in the heat maps analysis (appendix p 14).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the basic function of radiomics is to quantitatively analyze tumor regions of interest through a large number of radiomics characteristics, which can provide valuable diagnostic, prognostic or predictive information. Its purpose is to explore and use these information resources to develop diagnostic, predictive, or prognostic imaging omics models to support personalized clinical decision-making and improve individualized treatment options [26] [28] . Histopathology is the gold standard of clinical tumor diagnosis, directly related to the development of treatment and the evaluation of prognosis.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, leveraging AI and digital pathology has shown significant promise in cancer diagnosis ( 38 , 49 ). Remarkably, there have been attempts to integrate pathological section data and radiological data ( 96 ), which is called a new term as radopathomics. The fusion signature combining information from distinct dimensions could better predict discrepancies of treatment response.…”
Section: Future Challengesmentioning
confidence: 99%